2013
DOI: 10.1007/s00432-012-1367-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of early distant metastasis in women with breast cancer

Abstract: A significant fraction of breast cancer patients experienced early metastasis. Our data suggest that tumour stage, size and lymph node involvement are major predictors of metastasis. Her-2/neu over-expression alone is not a strong predictor of early metastasis but triple negative breast cancers belong to an aggressive subgroup with early metastatic capacity. Young, premenopausal patients may benefit from aggressive surveillance and treatment since they tend to present with early visceral spread.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 16 publications
8
37
0
Order By: Relevance
“…In a study by Erick Sta et al which focused on factors effective in less than 2-year recurrence, the major factors effective in early recurrence were tumor stage, and size and lymph node status. This study showed that her2 receptor overexpression was not the only determining factor, but triple negative breast cancer patients were likely to experience early metastasis (9).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In a study by Erick Sta et al which focused on factors effective in less than 2-year recurrence, the major factors effective in early recurrence were tumor stage, and size and lymph node status. This study showed that her2 receptor overexpression was not the only determining factor, but triple negative breast cancer patients were likely to experience early metastasis (9).…”
Section: Discussionmentioning
confidence: 75%
“…Breast cancer patients are at recurrence risk even years after receiving treatment which is the highest during the 2 -3 years after detection of the primary tumor (9). Distant metastasis is the most prevalent form of recurrence and the main cause of death in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies revealing a similar correlation in other tumor types have delivered conflicting results: For example, in a breast cancer study, a positive correlation between the age and visceral metastases was identified (31). In another study on melanoma, the prognosis worsened with age, whereas the number of CD168-positive sentinel nodes decreased (32).…”
Section: Discussionmentioning
confidence: 99%
“…About 10% to 15% of breast cancer patients have distant metastases within 2 years, which significantly reduced the 5 year survival rate [1]. Staging, Tumor size and lymph node metastasis are important prognostic factors for breast cancer metastasis, and in those factors, lymph node metastasis is the most important effect on ductal breast cancer prognosis.…”
Section: Discussionmentioning
confidence: 99%